Proceedings of the International Scientific Conference the Fifth Technological Order: Prospects for the Development and Moderni 2020
DOI: 10.2991/assehr.k.200113.166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Changes in Water Use Indicators in the Agricultural Sector in the South of Western Siberia

Abstract: In this paper, we made an assessment of the change in water use indicators of the agro-industrial sector (AIS) in the south of Western Siberia at the present stage of production and economic activity development. In order to solve planned tasks, an assessment of surface water resources was given in detail in the context of the entities of the south of Western Siberia of Russia; an analysis of the water availability of the studied agricultural sector area was carried out. The temporal dynamics of the main chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…During the analysis between 2018 and 2021, it can be concluded that in 2018, emissions of solid substances increased by 42.69% compared to 2021, but 0.5% less was captured and neutralized [5,6,7].…”
Section: Resultsmentioning
confidence: 99%
“…During the analysis between 2018 and 2021, it can be concluded that in 2018, emissions of solid substances increased by 42.69% compared to 2021, but 0.5% less was captured and neutralized [5,6,7].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that they have worked out their technically acceptable depreciation period, which guarantees their reliable operation. As a result of the physical deterioration of pipelines and fittings, it becomes necessary to modernize equipment and structures [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%